Vaccination Against Tuberculosis: Revamping BCG by Molecular Genetics Guided by Immunology - Kaufmann, Stefan H. E. (Frontiers in Immunology, 2020)
Tuberculosis (TB) remains a major health threat. Although a vaccine has been available for almost 100 years termed Bacille Calmette-Guérin (BCG), it is insufficient and better vaccines are urgently needed. This treatise describes first the basic immunology and pathology of TB with an emphasis on the role of T lymphocytes. Better understanding of the immune response to Mycobacterium tuberculosis (Mtb) serves as blueprint for rational design of TB vaccines. Then, disease epidemiology and the benefits and failures of BCG vaccination will be presented. Next, types of novel vaccine candidates are being discussed. These include: (i) antigen/adjuvant subunit vaccines; (ii) viral vectored vaccines; and (III) whole cell mycobacterial vaccines which come as live recombinant vaccines or as dead whole cell or multi-component vaccines. Subsequently, the major endpoints of clinical trials as well as administration schemes are being described. Major endpoints for clinical trials are prevention of infection (PoI), prevention of disease (PoD) and prevention of recurrence (PoR). Vaccines can be administered either pre-exposure or post-exposure with Mtb. A central part of this treatise is the description of the viable BCG-based vaccine, VPM1002, currently undergoing phase III clinical trial assessment. Finally, new approaches which could facilitate design of refined next generation TB vaccines will be discussed.